Kewenangan Pemerintah Daerah Dalam Pemberian Hak Milik Atas Tanah Bagi Transmigran Di Kabupaten Maluku Tengah - Nathalia Tanikwele; Salmon Eliazer Marthen Nirahua; Erick Stenly Holle (Faculty of Law, Universitas Pattimura, 2023)
Introduction: Transmigration is a development program that takes place by providing facilities by the government to transmigrants.Purposes of the Research: The purpose of this study is to analyze and determine the obligations of local governments. And to analyze and know the legal certainty of the Governing law.Methods of the Research: This research is a normative research that refers to the laws and regulations and legal materials related to the substance of the study, then connected with the subject matter in this study. The approach taken in this study is the statutory approach (statute approach) and conceptual approach (conceptual approach).Results of the Research: The results of the study, namely, land with the status of property rights of transmigrants of the settlement unit of Central Maluku regency, Seram Utara Barat district, turned out to be used for oil palm companies, so the right to obtain 1 hectare of land that has not been obtained until now from the transmigrants cannot be owned.